Perbandingan Perkembangan Pengelolaan Pantai Pandawa Sebagai Daya Tarik Wisata Di Desa Kutuh, Kecamatan Kuta Selatan, Kabupaten Badung - Ni Kadek Dina Medinawati; Ida Bagus Suryawan (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2017)
Pandawa beach officially launched by village governor in 2011, that then accepted as a tourist attraction by Badung government in 2014. As a tourist attraction, Pandawa beach had been given much changes just for five period of time. On it’s developing, on year of 2016 researcher heard some issues like changing management and divisioning tourist area at beach. According from these issues, the purposed of this reasearch is to compare management development at Pandawa beach in 2011 with 2016, that hope could give some depicts management changes that had been done by Pandawa beach management. This reasearch used some data collected technic, they were interview, observation, and documentation. The informants divided by based informant whom is Bendesa Adat Kutuh and key informants whom are manager and adiministration staff in Pandawa beach management. Analyze data was used comparative overtime analysis. The result of this comparison shows there are changes at each management function in Pandawa beach development, therefore from planning side, organizing, directing, and controlling. In planning side, alteration happened at nature attraction aspec, amenity, accessibility, tourist activity pattern, and institutional. Approach model which is use in Pandawa managemnt is model in form of the element manager’s governing body. To face these developments, manager of Pandawa beach must do some adviser for human resources intensively, re-evalution about future construction at beach area, and clarity management portion to stakeholders. Keywords: pandawa beach, beach development, management comparison